A novel approach to medical radioisotope production using inverse kinematics: A successful production test of the theranostic radionuclide 67Cu. (July 2019) - Souliotis, G.A.; Rodrigues, M.R.D.; Wang, K.; Iacob, V.E.; Nica, N.; Roeder, B.; Tabacaru, G.; Yu, M.; Zanotti-Fregonara, P.; Bonasera, A.
Abstract: A novel method for the production of important medical radioisotopes has been developed. The approach is based on performing the nuclear reaction in inverse kinematics, namely sending a heavy-ion beam of appropriate energy on a light target (e.g. H, d, He) and collecting the isotope of interest. In this work, as a proof-of-concept, we studied the production of the theranostic radionuclide 67 Cu (T1/2  = 62 h) via the reaction of a 70 Zn beam at 15 MeV/nucleon with a hydrogen gas target. The 67 Cu radionuclide alongside other coproduced isotopes, was collected after the gas target on an aluminum catcher foil and their radioactivity was measured by off-line γ -ray analysis. After 36 h post irradiation, apart from the product of interest 67 Cu, the main radioimpurity coming from the 70 Zn + p reaction was 69 m Zn (T1/2  = 13.8 h), which can be reduced by further radio-cooling. Moreover, along with the radionuclide of interest produced in inverse kinematics, the production of additional radioisotopes is possible by making use of the forward-focused neutrons from the reaction and allowing them to interact with a secondary target. A preliminary successful test of this concept was realized in the present study. The main requirement to obtain activities appropriate for preclinical studies is the development of high-intensity heavy-ion primary beams. Highlights: Production of the theranostic radionuclide 67 Cu in inverse kinematics. Production reaction: 70 Zn (15 MeV/nucleon) beam on a hydrogen gas target. Obtained activity of 67 Cu and other coproduced radioisotopes. Compared with theoretical estimates. Discussion of optimization steps to produce 67 Cu and other medical radioisotopes in inverse kinematics.